2013
DOI: 10.1161/jaha.113.000134
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of TDAG51 Protects Against Atherosclerosis by Modulating Apoptosis, Cholesterol Efflux, and Peroxiredoxin‐1 Expression

Abstract: BackgroundApoptosis caused by endoplasmic reticulum (ER) stress contributes to atherothrombosis, the underlying cause of cardiovascular disease (CVD). T‐cell death‐associated gene 51 (TDAG51), a member of the pleckstrin homology‐like domain gene family, is induced by ER stress, causes apoptosis when overexpressed, and is present in lesion‐resident macrophages and endothelial cells.Methods and ResultsTo study the role of TDAG51 in atherosclerosis, male mice deficient in TDAG51 and apolipoprotein E (TDAG51−/−/Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 65 publications
(140 reference statements)
0
21
1
Order By: Relevance
“…Superoxide generation was measured, as previously, with dihydroethidium (DHE) staining technique [16,30] in rat VSMC treated for 18 h with the endoplasmic reticulum stress inducer tunicamycin (1 mg/ml), the endoplasmic reticulum stress inhibitor 4-PBA (1 mmol/l) or tunicamycin in combination with 4-PBA. Images were captured as described above.…”
Section: Fluorescence Microscopymentioning
confidence: 99%
“…Superoxide generation was measured, as previously, with dihydroethidium (DHE) staining technique [16,30] in rat VSMC treated for 18 h with the endoplasmic reticulum stress inducer tunicamycin (1 mg/ml), the endoplasmic reticulum stress inhibitor 4-PBA (1 mmol/l) or tunicamycin in combination with 4-PBA. Images were captured as described above.…”
Section: Fluorescence Microscopymentioning
confidence: 99%
“…However, another study showed that PHLDA1 played no role in T‐cell apoptosis [Oberg et al, ]. Furthermore, it was reported to have a different function including atherogenesis regulation [Hossain et al, , ], and follicular stem cell marker [Sellheyer and Krahl, ]. Basseri et al suggested that PHLDA1 is involved in energy homeostasis, at least in part, by regulating lipogenesis in liver, and white adipose tissue [Basseri et al, ].…”
mentioning
confidence: 99%
“…Mouse tissue samples were prepared as previously described by Hossain et al (24). Briefly, following fixation with 10% neutral buffered formalin, hearts were embedded in paraffin.…”
Section: Quantification Of Lesion Areamentioning
confidence: 99%
“…Immunohistochemical staining of atherosclerotic lesions was performed as previously described (9,24,25). Tissue was fixed with formalin and embedded in paraffin.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%